Sodium Sulfite Exacerbates Allograft Vasculopathy and Affects Tryptophan Breakdown in Murine Heterotopic Aortic Transplantation. (8th April 2019) - Sucher, Robert; Hautz, Theresa; Mohr, Elisabeth; Mackowitz, Maximilian; Mellitzer, Vanessa; Steger, Christina; Cardini, Benno; Resch, Thomas; Margreiter, Christian; Schneeberger, Stefan; Brandacher, Gerald; Fuchs, Dietmar; et al.
Abstract : Graft vasculopathy is the main feature of chronic rejection in organ transplantation, with oxidative stress being a major trigger. Inflammation-associated prooxidant processes may be controlled by antioxidants; however, interference with redox-regulated mechanisms is a complex endeavor. An essential feature of the cellular immune response is the acceleration of tryptophan (Trp) breakdown, leading to the formation of several bioactive catabolites. Long-term activation of this immunobiochemical pathway contributes to the establishment of a tolerogenic environment, thereby supporting allograft survival. Herein, the impact of the antioxidant sodium sulfite on the development of graft vasculopathy was assessed in murine aortic transplantation. Allogeneic (BALB/c to C57BL/6) heterotopic murine aortic transplantations were performed. Animals were left untreated or were treated with 10 μ l of 0.1 M, of 0.01 M sodium sulfite, or of 0.1 M sodium sulfate, intraperitoneally once/day, until postoperative day (POD) 100. Grafts were assessed by histology, immunohistochemistry, and adhesion molecule gene expression. Serum concentrations of tryptophan and its catabolite kynurenine (Kyn) were measured. On day 100, graft vasculopathy was significantly increased upon treatment with 0.1 M sodium sulfite, compared to allogeneic untreated controls (p = 0.004 ), which correlated with a significant increase of α -smooth-muscle-actin, Vcam-1, and P-selectin. Serum Kyn concentrations increased in the allogeneic control group over time (p < 0.05, POD ≥ 50 ), while low-dose sodium sulfite treatment (0.01 M) treatment resulted in a decrease in Kyn levels over time (p < 0.05, POD ≥ 10 ), compared to the respective baselines (p < 0.05 ). Longitudinal analysis of serum metabolite concentrations in the different treatment groups further identified an overall effect of sodium sulfite on Kyn concentrations. Antioxidative treatment may result in ambivalent consequences. Our data reveal that an excess of antioxidants like sodium sulfite can aggravate allograft vasculopathy, which further highlights the challenges associated with interventions that interfere with the complex interplay of redox-regulated inflammatory processes.